1992
DOI: 10.1128/aem.58.2.551-556.1992
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal colonization potential of turbot (Scophthalmus maximus)- and dab (Limanda limanda)-associated bacteria with inhibitory effects against Vibrio anguillarum

Abstract: Of more than 400 bacteria isolated from turbot (Scophthalmus maximus), 89 have previously been shown to inhibit the in vitro growth of the fish pathogen Vibrio anguiUarum. The aim of the present study was to investigate the potential of seven of these strains, as well as of intestinal isolates (four strains) from a closely related fish, dab (Limanda limanda), for colonizing farmed turbot as a means of protecting the host from infection by V. anguillarum. In addition, the inhibitory effect of these strains on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(77 citation statements)
references
References 25 publications
1
75
0
1
Order By: Relevance
“…In conclusion, probiotics in vivo may become more competitive than predicted from experimental observations of their growth patterns or their starting population density as the production of antimicrobial metabolites or better attachment ability lead to inhibition in vitro. The production or e¡ect of inhibitory metabolites depends on the media on which the probiotic is cultured [39]. Further tests examining the production of antimicrobial metabolites in ¢sh mucus need to be carried out to verify preliminary conclusions from this study and account for the factors that a¡ect the ranking of candidate probiotics in vivo.…”
Section: Discussionmentioning
confidence: 92%
“…In conclusion, probiotics in vivo may become more competitive than predicted from experimental observations of their growth patterns or their starting population density as the production of antimicrobial metabolites or better attachment ability lead to inhibition in vitro. The production or e¡ect of inhibitory metabolites depends on the media on which the probiotic is cultured [39]. Further tests examining the production of antimicrobial metabolites in ¢sh mucus need to be carried out to verify preliminary conclusions from this study and account for the factors that a¡ect the ranking of candidate probiotics in vivo.…”
Section: Discussionmentioning
confidence: 92%
“…Only Mueller-Hinton agar supplemented with 2% NaCl allowed the demonstration of inhibitory effects of the tested bacteria. Olsson et al (1992) previously found differences in the bacteriocin production of intestinal fish microbiota against V. anguillarum depending on the media used.…”
Section: Inhibitory Effectsmentioning
confidence: 97%
“…The production of antibacterial substances by bacteria isolated from the digestive tract of fish has been demonstrated in several studies (Schrùder, Clausen, Sandberg & Raa 1980;Strùm 1988;Westerdahl, Olsson, Kjelleberg & Conway 1991;Olsson, Westerdahl, Conway & Kjelleberg 1992;Bergh 1995;Sugita, Shibuya, Shimooka & Deguchi 1996;Jo Èborn, Olsson, Westerdahl, Conway & Kjelleberg 1997;Sugita, Shibuya, Hanada & Deguchi 1997;Gram, Melchiorsen, Spanggard, Huber & Nielsen 1999;Ringù 2000;Ringù, Bendiksen, Wesmajervi, Olsen, Jansen & Mikkelsen 2000). Therefore, the final aim was to evaluate the antibacterial potential of autochthonous bacteria isolated from the hindgut of Arctic charr before and after challenge with A. salmonicida.…”
Section: Introductionmentioning
confidence: 99%